A Collaborative Partnership Model between Faculty of Education and La-orutis Demonstration School for Developing Excellent Teaching Competencies of Pre-service Early Childhood Teachers - Chaleysub, Sukum; Sawetsomboon, Sirinda; Sakulhom, Venus; Tungdamnernsawad, Supaporn (Mahachula Academic Journal, 2026)
This qualitative research aimed to: (1) study the characteristics and processes ofcollaboration; (2) study the components of collaborative synergy and their relationships affecting teaching competency development; and (3) develop a collaborative partnershipmodel between the Faculty of Education and La-orutis Demonstration School for developing excellent teaching competencies of pre-service early childhood teachers.The key informants consisted of 15 administrators and 246 faculty members, teachers,and students. Research instruments included semi-structured interview protocols andopen-ended questionnaires, validated with IOC values ranging from 0.80-1.00. Data wereanalyzed using content analysis and thematic analysis. The findings revealed that: (1) the characteristics of collaborative synergy includedacademic integration, human resource and support system development, and collaborative culture and co-learning creation, with operational processes forminga co-learning cycle through Co-Teaching, Co-Research, and Co-Reflection mechanisms;(2) excellent teaching competencies comprised valuing learner diversity, designing andimplementing developmental learning activities, teamwork and professional collaboration, and professional self-development; and (3) the “ASPIRE MODEL” collaborative partnership model consisted of Alliance, Supervisor, Practitioner, Integration, Refinement, and Excellence.